2015
DOI: 10.1128/aem.02745-14
|View full text |Cite
|
Sign up to set email alerts
|

An In Planta -Expressed Polyketide Synthase Produces ( R )-Mellein in the Wheat Pathogen Parastagonospora nodorum

Abstract: dParastagonospora nodorum is a pathogen of wheat that affects yields globally. Previous transcriptional analysis identified a partially reducing polyketide synthase (PR-PKS) gene, SNOG_00477 (SN477), in P. nodorum that is highly upregulated during infection of wheat leaves. Disruption of the corresponding SN477 gene resulted in the loss of production of two compounds, which we identified as (R)-mellein and (R)-O-methylmellein. Using a Saccharomyces cerevisiae yeast heterologous expression system, we successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 63 publications
1
50
1
Order By: Relevance
“…The capacity of AOH to affect seed germination was also assessed. Unlike what we had observed for (R)-mellein in a previous study (39), AOH did not inhibit the germination of wheat and barrel medic seeds (data not shown). We have also tested the antimicrobial activity of AOH against Escherichia coli, Saccharomyces cerevisiae, Zymoseptoria tritici, and three environmental bacterial strains isolated from field wheat samples (Bacillus cereus, a Flavobacterium sp., and Sphingobacterium multivorum) (see the methods in the supplemental material).…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…The capacity of AOH to affect seed germination was also assessed. Unlike what we had observed for (R)-mellein in a previous study (39), AOH did not inhibit the germination of wheat and barrel medic seeds (data not shown). We have also tested the antimicrobial activity of AOH against Escherichia coli, Saccharomyces cerevisiae, Zymoseptoria tritici, and three environmental bacterial strains isolated from field wheat samples (Bacillus cereus, a Flavobacterium sp., and Sphingobacterium multivorum) (see the methods in the supplemental material).…”
Section: Resultscontrasting
confidence: 55%
“…Using both reverse genetics and heterologous expression, we recently identified the P. nodorum PKS gene responsible for production of R-(Ϫ)-mellein, which exhibited antigerminative activity (39). Here, using a similar approach, we unequivocally demonstrated that SnPKS19, which is highly similar to the A. alternata pksI product (86% protein identity), is solely responsible for the biosynthesis of AOH in P. nodorum.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The metabolite products encoded by these gene clusters are mostly unknown. Recently, we characterized the PKS genes in P. nodorum that encode an anti‐germinative compound ( R )‐mellein (Chooi et al ., ) and the mycotoxin alternariol (Chooi et al ., ). As part of our ongoing effort to understand the chemistry and pathobiology of P. nodorum , we focus on a P. nodorum polyketide synthase (PKS) gene cluster ( SNOG_08608 ‐ SNOG_08616 ) in this study.…”
Section: Introductionmentioning
confidence: 99%
“…When SN477 , was cloned from cDNA under the ADH2 promoter and transformed into S. cerevisiae BJ5464-NpgA, ( R )-mellein was produced by the yeast host, revealing that SN477 is the only enzyme required for ( R )-mellein synthesis. Though ( R )-mellein showed no relevance to the virulence against wheat, it was able inhibit the germination of wheat seeds (Chooi et al, 2015). …”
Section: Yeast As a Platform For Studying The Function Of Fungal Imentioning
confidence: 99%